Teachers' Consideration on Students' Learning Strategies in Speaking on Blended Leaning: is it proper? - Berliana, Winny; Ardi, Havid (Jurnal Bahasa dan Sastra, 2024)
Since the Covid-19 pandemic hit the world, blended learning techniques have become very important in the learning process. Therefore, this research aims to find out students' learning strategies, teachers' and students' use of learning media, and whether students' learning strategies align with teachers' and students' choices of learning media for speaking skills in blended learning during the Covid-19 pandemic. This is a qualitative research study conducted through questionnaires and interviews. The researcher employed a purposive sampling technique to select 26 students from class XI Natural Science, class XI Social Science, and 3 English teachers from a public school in Jambi Province. The findings reveal that, firstly, students in XI Natural Science and XI Social Science predominantly used metacognitive strategies. However, the lowest strategy employed by XI Natural Science students was the cognitive strategy, while for XI Social Science students, it was the social strategy. Secondly, the most frequently used learning media by the teachers was E-book. Thirdly, this research demonstrates that the learning strategies employed by students are consistent with the learning media chosen by both teachers and students. Furthermore, the implications of this study are that teachers can gain insights on how to teach students to enhance their speaking abilities, and English teachers can benefit from adapting the learning media to the preferences of their students.